EKSTRAKK UMBI BAWANG DAYAK (Eleutherine palmifolia (L.) Merr.) SEBAGAI PEREDUKSI ION PERAK DALAM SINTESIS NANOPARTIKEL PERAK - Normaningsih Rahayu; Gusrizal Gusrizal; Nurlina Nurlina (Tanjungpura University, 2020)
Silver nanoparticles (AgNPs) are one of the best plasmonic candidates that have been used in Surface Plasmon Resonance (SPR)-based nanosensors for the detection of metallic ions. In this research, AgNPs were prepared by the method using Eleutherine palmifolia (L.) Merr root ethanol extract. Silver nanoparticles were synthesized by reduction of silver nitrate with Eleutherine palmifolia (L.) Merr. Tuber extract (concentration of extract = 0,01%, pH = 11, volume ratio 1:1) in the boiling water bath for 90 minutes. The formation of silver nanoparticles was indicated by the appearance of yellow color and monitored using a UV-Visible spectrophotometer. The spectra showed the maximum peak at 401-405 nm. The resulted silver nanoparticles with the size of 10-20 nm were stable at least for 16 weeks.